An innovative approach of using online problem.based learning and case-based learning in teaching disaster nursing during the COVID-19 pandemic - Yin-Ji Liang; Wei-Ju Chen; Shuang Zhou; Lin Wang; Qiu-Ying Liao; Wan-Xian Lu; Chen-Li Lin (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to evaluate the learning experience effect of online problem-based learning (PBL) and case-based learning (CBL) in teaching disaster nursing. Methods: According to the characteristics of online PBL and CBL, the revised curriculum experience questionnaire (CEQ) was used to evaluate the teaching quality. Cronbach's coefficient and the reliability of the split-half reliability questionnaire were calculated. The exploratory factor analysis of 26 items was carried out by principal component analysis and maximum variance rotation method. Kaiser-Meyer-Olkin (KMO) and Bartlett's tests were used to test the validity of the questionnaire. The comparison between groups was performed by one-way analysis of variance. Results: A total of 191 questionnaires were issued and 183 copies were recovered, with a recovery rate of 95.8%. The Cronbach's alpha coefficient of CEQ is 0.929, and the Cronbach's alpha coefficient of each dimension is between 0.713 and 0.924. After factor analysis, the KMO value was 0.817. The 26 items finally returned to 6 principal components, and all factor load values were above 0.7, indicating good factor analysis effect. This study found that students who learned disaster nursing had an ideal online learning experience, and the average value of CEQ was 3.74 ± 0.42. In particular, male students, senior students or medical students had a higher curriculum experience score. In addition, compared with the national recruitment, the international students have higher curriculum experience score on the dimension of Appropriate Assessment Scale, indicating that the international students are more inclined to use online PBL and CBL. Conclusions: Using the revised CEQ is an innovative approach to evaluate the effect of online PBL and CBL in teaching disaster nursing, which can improve students' experience and curriculum quality.